Transcriptomic and Single-Cell Analysis Reveals Regulatory Networks and Cellular Heterogeneity in Mouse Primary Sjögren’s Syndrome Salivary Glands - Horeth, Erich; Oyelakin, Akinsola; Song, Eun-Ah Christine; Che, Monika; Bard, Jonathan; Min, Sangwon; Kiripolsky, Jeremy; Kramer, Jill M.; Sinha, Satrajit; Romano, Rose-Anne (Frontiers in Immunology, 2021)
Sjögren’s Syndrome (SS) is a chronic autoimmune disease of unknown etiology which primarily affects the salivary and lacrimal glands resulting in the loss of secretory function. Treatment options for SS have been hampered due to the lack of a better understanding of the underlying gene regulatory circuitry and the interplay between the myriad pathological cellular states that contribute to salivary gland dysfunction. To better elucidate the molecular nature of SS, we have performed RNA-sequencing analysis of the submandibular glands (SMG) of a well-established primary Sjögren’s Syndrome (pSS) mouse model. Our comprehensive examination of global gene expression and comparative analyses with additional SS mouse models and human datasets, have identified a number of important pathways and regulatory networks that are relevant in SS pathobiology. To complement these studies, we have performed single-cell RNA sequencing to examine and identify the molecular and cellular heterogeneity of the diseased cell populations of the mouse SMG. Interrogation of the single-cell transcriptomes has shed light on the diversity of immune cells that are dysregulated in SS and importantly, revealed an activated state of the salivary gland epithelial cells that contribute to the global immune mediated responses. Overall, our broad studies have not only revealed key pathways, mediators and new biomarkers, but have also uncovered the complex nature of the cellular populations in the SMG that are likely to drive the progression of SS. These newly discovered insights into the underlying molecular mechanisms and cellular states of SS will better inform targeted therapeutic discoveries.